10.1016/0967-0653(95)96331-x (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Social media influencers occupy a pervasive role in billions of users' daily digital lives, particularly among adolescents and young adults. Audiences develop parasocial engagement with these figures, including parasocial relationships (PSRs) and parasocial interactions (PSIs). Despite growing concern about their mental health implications, no prior meta-analysis has quantitatively synthesized this evidence. OBJECTIVE: This systematic review and meta-analysis aimed to estimate the associations between influencer-directed parasocial engagement and mental health outcomes, examine prespecified moderators, and evaluate the quality of the existing evidence base. METHODS: Seven databases (PsycINFO, Embase, MEDLINE, ERIC, PubMed, Web of Science, and Scopus) were searched from inception. Studies quantitatively assessing PSRs or PSIs with social media influencers and reporting mental health outcomes were eligible. A 3-level random-effects meta-analysis was conducted using Pearson r. Primary pooled estimates were calculated separately for positive or adaptive outcomes, and negative or maladaptive outcomes. Moderators examined included outcome domain, parasocial construct type, age group, gender, cultural region, and platform. RESULTS: Seventeen studies (52 effect sizes) were included. Parasocial engagement was positively associated with both positive (k=28; r=0.38, 95% CI 0.18-0.55) and negative outcomes (k=24; r=0.24, 95% CI 0.08-0.38), with positive effects significantly stronger. Well-being showed the largest effects (r=0.42), followed by social media addiction (r=0.33). PSI demonstrated stronger associations than PSR (r=0.56 vs 0.22). Effects were largest among adolescents (r=0.44) and in Eastern samples (r=0.61 vs 0.29). No evidence of publication bias was detected (Egger P=.94; fail-safe N=18,643). CONCLUSIONS: Parasocial engagement functions as a psychological double-edged sword, reliably linked to both enhanced well-being and problematic engagement. Positive mental health outcomes, particularly those involving well-being, were generally stronger and more consistent than negative ones. These findings suggest that parasocial engagement should not be understood as uniformly beneficial or harmful; rather, its psychological meaning depends on the outcome domain, parasocial construct type, developmental stage, and cultural context. Future longitudinal, mechanism-based research with diverse samples is needed to clarify when parasocial engagement is most beneficial or harmful.